2013
DOI: 10.1177/0267659113481398
|View full text |Cite
|
Sign up to set email alerts
|

The utility and prognostic value of dipyridamole technetium-99m sestamibi myocardial perfusion imaging SPECT in predicting perioperative cardiac events following non-cardiac surgery

Abstract: The incidence of perioperative cardiac events is higher in patients with abnormal MPI. Dipyridamole 99m Tc-MIBI myocardial perfusion imaging can accurately detect the preoperative cardiac risk of patients undergoing major non-cardiac surgery. Based on these findings, the occurrence of perioperative cardiac events in patients with abnormal MPI should be considered, especially in the older age population (age ≥70).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
2
5
0
Order By: Relevance
“…This finding is consistent with the previous report showing good agreement between DS SPECT and DSE in the recognition of inotropic reserve in infarcted areas [13]. Panza et al [4] mentioned 68% agreement between DSE and thallium scan and Bax et al [1] found 72% agreement between DSE and technetium scan. However, the prior studies did not analyze these results with other methods of viability, such as PET measurements of viability or functional recovery.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This finding is consistent with the previous report showing good agreement between DS SPECT and DSE in the recognition of inotropic reserve in infarcted areas [13]. Panza et al [4] mentioned 68% agreement between DSE and thallium scan and Bax et al [1] found 72% agreement between DSE and technetium scan. However, the prior studies did not analyze these results with other methods of viability, such as PET measurements of viability or functional recovery.…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were reported by Panza et al [4] who tested 201thallium imaging with dobutamine echocardiography, and demonstrated that a large number of segments with 201 thallium uptake may lack contractile reserve. The difference may arise from the mechanisms of the detection of myocardial viability by the two modalities; the cellular processes dependable for a positive inotropic response to adrenergic stimulation require a higher degree of myocyte functional integrity than those responsible for thallium uptake [4].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…and other tests such as pulmonary function 67 , echocardiography 68 and cardiac perfusion scans 69 . Liver surgery is increasingly offered to older patients with co-existing co-morbidity.…”
Section: Assessment Of Fitness For Surgerymentioning
confidence: 99%